Pengaruh Panjang Serat Kulit Bambu Terhadap Sifat Mekanik Beton (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2015)
Concrete has significant deficiencies, which have a low tensile strength. The addition of fiber is one alternative to overcome these shortcomings. Bamboo fiber is a natural fiber that is readily available and relatively fast growth of bamboo. Fibers made of bamboo on the skin without the book.This study aimed to examine the effect of fiber length of bamboo bark against concrete compressive strength, tensile strength of concrete, and the flexural strength of concrete. The study was conducted by making a diameter cylindrical specimen of 150 mm and a height of 300 mm and a beam with a length of 600 mm, width 150 mm, and a height of 150 mm. Used fiber content is 0.5 wt% of aggregate fraction with variation in the length of 2.5 cm (BS-2.5), 5 cm (BS-5), and a 7.5 cm (BS-7.5). Concrete without fiber (BN) is also made as a comparison.The results showed BN compressive strength is 26.97 MPa, BS-2.5 32.82 MPa (up 21.68%), BS-5 27.73 MPa (up 2.80%), BS-7.5 25 , 18 Mpa (down 6.64%), and BS-10 31.69 MPa (up 17.48%). BN tensile strength is 2.31 Mpa, BS-2.5 2.92 MPa (up 26.53%), BS-5 at 2.92 MPa (down 1.02%), BS-7.5 2.07 Mpa (down 10.20%), and BS-10 2.59 MPa (up 12.24%). BN flexural strength was 5.20 MPa, BS-2.5 4.77 MPa (down 8.28%), BS-5 5.13 MPa (down 1.31%), BS-7.5 4.69 Mpa (down 9.80%), and BS-10 of 5.88 MPa (up 13.07%). From the results of this study concluded that the effect of fiber length 2.5 cm can increase the compressive strength and tensile strength respectively 21.68% and 26.53%. In the flexural strength testing biggest influence fiber length is the length of 10 cm that is equal to 13.07%.Keywords: Concrete fiber, long fiber, bamboo skin, compressive strength, tensile strength, flexural strength